Are plain radiographs reliable in Lichtman classification? - CANSÜ, CENGİZ EREN (TURKISH JOINT DISEASES FOUNDATION, 2020)
Objectives: This study aims to investigate the reliability of the Lichtman classification among residents, orthopedic surgeons, and hand surgeons. Materials and methods: This study was carried out with 30 male observers (mean age 37.8 years; range, 26 to 62 years) who agreed to participate in the study. All observers were orthopedic surgeons. The observers were separated into three groups that consist of 10 residents, 10 orthopedic surgeons, and 10 hand surgeons. The anteroposterior and lateral wrist radiographs of 20 patients (12 males. 8 females; mean age 49 years; range, 38 to 74 years) diagnosed as Kienbock's disease were sent to observers via e-mail as a survey. All 40 radiographs were asked to be kept classified. Results: The classification of Kienbock's disease was analyzed by 30 observers on 40 digital radiographs. The overall agreement with the Lichtman classification was fair within all of the observers (kappa=0.203). When groups were evaluated within themselves, the agreement level was found poor in group 1 (kappa=0.162) and fair in group 2 (kappa=0.210) and group 3 (kappa=0.252). Conclusion: A useful classification system in orthopedics and traumatology should classify the type of musculoskeletal disorder reliably, facilitate communication in clinical practice, guide preoperative planning, and enable comparison of results between studies. The Lichtman classification alone is insufficient and should be supported by other imaging and measurement techniques.
Keywords: Agreement; classification; Kienbock; Lichtman; reliability; KIENBOCKS-DISEASE; RELIABILITY; REPRODUCIBILITY